Exercise-induced Hypertension and Carotid Intima-media Thickness in Male Marathon Runners - Yoon, Eun Sun; Kim, Young-Joo (International Journal of Sports Medicine, 2024)
This study aimed to identify the relationship between exercise-induced hypertension and carotid artery intima-media thickness in long-distance runners. Sixty healthy male runners aged 40 to 60 years were assigned to the following three groups based on resting blood pressure and maximal systolic blood pressure during a maximal exercise test: normal blood pressure response, exercise-induced hypertension, and complex hypertension. An exaggerated systolic blood pressure response was defined as a maximal systolic blood pressure+≥+210 mmHg during the maximal exercise test, while carotid intima-media thickness was measured using B-mode ultrasonography. The carotid intima-media thickness mean values were the highest in the complex hypertension group (0.72±0.11 mm), followed by exercise-induced hypertension (0.62±0.12 mm) and normal blood pressure groups (0.55±0.13 mm), with a significant difference between the groups (p+<+0.002). In linear regression analysis, the mean intima-media thickness was independently associated with age (p=0.015) and maximal systolic blood pressure (p=0.046) but not with resting systolic blood pressure. These results suggest that exercise-induced hypertension is associated with carotid intima-media thickness, a surrogate marker of cardiovascular disease, in long-distance runners. Therefore, evaluating the blood pressure response during exercise is important for the early detection of potential cardiovascular disease risks in long-distance runners.
Keywords: marathon; exercise-induced hypertension; carotid intima-media thickness